Digital Picture Card Media Based on Mother Tongue Assisted with Artificial Intelligence in Literacy Learning for Early Grades - Sayangan, Yohanes Vianey (International Journal of Elementary Education, 2024)
Elementary school students' literacy skills are still relatively low, this is because students are not yet accustomed to accomplishing literacy activities regularly. This research aims to analyze the effectiveness of digital picture media using mother tongue assisted with AI in literacy learning for early-class students. This study uses a descriptive analysis method with a qualitative approach. Data were obtained through a variety of methods, named: observation, interviews, and analysis of documentation material. In Interviews, the data was collected through the key informants consisting of the principal, vice principal, class teachers, parents, and the retired school principal. The data were analyzed using interactive data rolling, starting from data collection, data presentation, data reduction, and verification of withdrawal. The results of using digital picture card media in literacy learning for early-grade students, digital image media assisted by artificial intelligence can stimulate students' participation and creative abilities to learn, recognize letters, and read simple words and sentences. The role of the mother tongue in language instruction is very important. It helps early-grade students to grasp literacy learning. Third, the use of picture card media based on the mother tongue and artificial intelligence technology is very effective in improving students' abilities in studying literacy, especially reading for early-grade students. These findings reflect that the use of mother tongue-based digital picture media can improve student's abilities in literacy learning.